An Analysis of Students Interpersonal Intelligence in Dance Extracurricular Activities at Elementary School - Putri, Megayanti Hendiana; Sukarno, Sukarno; Daryanto, Joko (Social, Humanities, and Educational Studies (SHES): Conference Series, 2026)
Dance extracurricular activities in elementary schools involve student social interaction but are not always optimally used to develop interpersonal intelligence. This study aims to analyze students’ interpersonal intelligence in dance extracurricular activities at Pondok 01 State Elementary School and identify supporting and inhibiting factors. This research uses a qualitative case study approach with 12 students and one instructor selected through purposive sampling. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results show that students’ interpersonal intelligence developed well, as reflected in their ability to communicate, cooperate, adapt, and resolve conflicts during activities. Supporting factors include student enthusiasm, active teacher involvement, and performance opportunities, while inhibiting factors are limited practice time, student character differences, and uneven discipline. Thus, dance extracurricular activities can effectively develop interpersonal intelligence if managed systematically and continuously.